Control of Bipolaris sorokiniana in wheat and interference on diazotrophic endophytes - Iurkiv, Luciana; Dildey, Omari Dangelo Forlin; Coltro-Roncato, Sidiane; Gonçalves-Trevisoli, Edilaine Della Valentina; Rissato, Bruna Broti; Guimarães, Vandeir Francisco; Stangarlin, José Renato (Scientia Agraria Paranaensis, 2017)
The induced resistance efficiency in the control of phytopathogens is recognized, however little is known about its interference on non-target microorganisms. The present study aimed to verify the induction of peroxidase activity by the use of acibenzolar-S-methyl (ASM), mannanoligosaccharide (MOS) and Bacillus cereus inductor in the control of spot blotch wheat disease and its interference on the non-target microorganism Azospirillum brasilense. The experiment was conduced under greenhouse condition. The experimental design was a randomized block in a factorial schema 4 x 2 x 2, with four replications. The first factor “Resistance Inductors” was constituted by ASM, MOS and B. cereus inductors and water (control). The second factor “Pathogen” was constituted by the presence or absence of B. sorokiniana pathogen. The third factor “PPGR” was made up by the presence or absence of the PPGR A. brasilense. Disease severity, peroxidase activity and quantification of endofitic diazotrofic microorganisms were assessed. There was a reduction in the disease severity by the use of resistance inductors. The activity of peroxidase was estimulated by MOS. Direct interference of the inductors on endophytic diazotrophic microorganisms was not observed.